Shear capacity of stud-groove connector in Glulam-concrete composite structure - Xie, Lan; He, Guojing; Wang, Xiaodong; Gustafsson, Per Johan; Crocetti, Roberto; Chen, Liping; Li, Li; Xie, Wenhui (BioResources, 2017)
A timber-concrete composite structure (TCC) is economically and environmentally friendly. One of the key design points of this kind of structure is to ensure the reliability of the shear connectors. The objective of this paper is to study the mechanical property of stud-groove-type connectors and to provide shear capacity equations for stud-groove connectors in timber-concrete composite structures. Based on the Johansen Yield Theory (European Yield Model), some mechanical models and capacity equations for stud-groove-type connectors in timber-concrete structures were studied. Push-out specimens with different parameters (stud diameter, stud length, groove width, and groove depth) were tested to obtain the shear capacity and slip modulus. The experimental strengths were used to validate equations given in the paper. The shear capacity and slip modulus of stud-groove-type connectors was in direct proportion to the diameter of studs and the dimension of the groove. Comparison between the theoretical and the experimental shear strength results showed reasonable agreement. The highlight of this study on shear capacity equations could significantly reduce the push-out tests before investigating the other properties of TCC.
Keywords: Lamination slip modulus; Push-out tests; Shear capacity equation; Stud-groove connectors; Timber-concrete composite structure